Reconstruction of the ocean circulation in the subtropical western South Atlantic during the last 40,000 years - Pereira, Ligia Sauaya (2018)
The Atlantic meridional overturning circulation (AMOC) has a central role in the interhemispheric transport of heat and changes in its intensity are known to have profound impact on global climate. Disturbances in the AMOC are also supposedly associated with the past changes in marine productivity and oceanic uptake of atmospheric carbon dioxide, which contributed to the global climate changes that led to the termination of the last glacial cycle. Although the South Atlantic Ocean constitutes an important pathway for the return flow of the AMOC, the changing impacts of the AMOC especially in the subtropical western South Atlantic still remain elusive. In this study, high-resolution records of upper water column properties and productivity have been applied to reconstruct the evolution of oceanographic conditions in the subtropical western South Atlantic covering the last 40,000 years. The proxy records employed here are based both on faunal assemblages and on the stable oxygen isotopic composition of planktonic foraminifera from a marine sediment core collected off southern Brazilian continental margin (27°S). The main findings of the present study reveal, for the first time, enhanced primary productivity in the subtropical western South Atlantic during Heinrich Stadials along the last glacial, when the AMOC showed reduced strength. Additionally, this study reveals decreased primary productivity over the Last Glacial Maximum and the Younger Dryas, when the AMOC showed only moderate reductions. The most outstanding productivity decline is depicted after the Holocene inception, when the AMOC recovered its strength. Further, the findings of the present work also reveal that rather overall glacial-like conditions prevailed at the onset of the Holocene, before complete reinvigoration of the AMOC. Full interglacial configuration would only establish at approximately 9,000 years, when the AMOC fully recovered; although such interglacial setting would be abruptly interrupted during the Mid Holocene, accompanying a sudden reduction of the AMOC. Those findings suggest that the impact of the AMOC on the subtropical western South Atlantic would have played a critical role not only over the last glacial, but also throughout the glacial-interglacial transition and even under full interglacial conditions. The main hypothesis of this research is that the observed changes were triggered by the dynamics of the Brazil Current primarily driven by disturbances in the AMOC.